Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.7 Radical Expressions - R.7 Exercises - Page 75: 89



Work Step by Step

RECALL: $(a+b)^2=a^2+2ab+b^2$ Use the formula above with $a=\sqrt3$ and $b=\sqrt8$ to obtain: $(\sqrt3+\sqrt8)^2 \\=(\sqrt3)^2+2(\sqrt3)(\sqrt8) + (\sqrt8)^2 \\=3 + 2\sqrt{3\cdot8}+8 \\=11 + 2\sqrt{24}$ Factor the radicand so that one factor is a perfect square, then bring out the square root of the perfect square factor to obtain: $=11+2\sqrt{4(6)} \\=11+2(2)\sqrt6 \\=\color{blue}{11+4\sqrt6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.